MODERN METHODS IN TEACHING ENGLISH - Makhmudova Donokhan Bozorboevna (Journal of new century innovations, 2024)
Abstract: In this article, we look at the main modern methods of teaching English that are shaping the future of language education. From communicative language teaching to gamification and the Flipped Classroom model, these approaches are designed to enhance language acquisition, develop critical thinking skills, and empower students to become confident users of English.